Types of Code-Mixing Found in Natasha Surya’s TikTok - Putu Desi Anggerina Hikmaharyanti; Ni Putu Indira Anggita Hartawan (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2023)
This study classified the types of code-mixing contained in TikTok contents of Natasha Surya. The data sources of this research were taken from 5 TikTok videos which used many codemixing styles. This study applied a qualitative descriptive method in analyzing the data to elaborate the types of code-mixing found in the contents. The theory used in this study was the type of code-mixing theory proposed by Muysken (2000). Based on the analysis, there were two types of code-mixing; they were 5 insertions and 6 congruent lexicalizations. Insertion type was indicated by inserting a foreign word in a sentence while congruent lexicalization was a combination of more than one word shifting in a sentence to form a whole structural arrangement. Code-mixing was commonly used by bilingual people to show their skill in language and mixing words could raise the confidence. Further research was necessary to answer this hypothesis.